Biosynthesis of a range of ZnO nanoparticles utilising Salvia hispanica L. seed extract and evaluation of their bioactivity - Kiran Singh; Shweta Yadav (Scientific Reports)
Abstract Zinc deficiency precipitates considerable health problems in developing countries, affecting development, growth, and immunological function. The main issue is that zinc exhibits limited bioavailability in diets, sometimes compounded by the high concentration of phytate molecules in staple foods, which impedes zinc absorption. Nanoparticles offer a promising approach to improve zinc bioavailability and address deficiency through the application of advanced agricultural techniques. The study introduces a novel method for synthesizing Zinc oxide (ZnO) biometallic nanoparticles by employing aqueous extracts of Salvia hispanica L. (Chia seed) as a reducing and capping agent in an environmentally sustainable way. Their active phytoconstituents acted as a stabilising agent and facilitated the conversion of ionic zinc (Zn2+) into elemental zinc. The study synthesized the diverse forms of zinc oxide nanoparticles (NP-α, NP-β, NP-γ, NP-δ, NP-ε, and NP-η) utilising various molar concentrations (0.5mM, 1.0mM, 3.0mM, 5.0mM, 7.0mM, and 9.0mM) of a precursor solution, zinc nitrate [(ZnNO3)2]. The synthesized NPs were evaluated using UV-Vis spectroscopy, FTIR spectroscopy, XRD, SEM, EDX, TEM, SAED, and HR-TEM methods to determine their characteristics. The standard particle size varies from 40 to 80 nm, exhibiting a consistent hexagonal morphology and a polydispersed characteristic with minimal size fluctuation. The molarity substantially influenced the shape of NPs, particularly concerning their size and surface area. An in vitro evaluation was performed to investigate the antibacterial activity against Staphylococcus aureus and the possible degradation of the hazardous dye Congo red. The particles exhibited antibacterial efficacy at a concentration of 40 ppm ZnO, antidiabetic qualities at 10 µl/ml ZnONPs, antioxidant activity at concentrations ranging from 100 to 900 µl/ml showing 89.47 ± 0.022 µg AAE/mg, maximum activity with total antioxidant capacity (TAC), and dye degradation potential at a concentration of 50 mg ZnONPs, revealed 50.78% CR degradation after 90 min of irradiation. Additionally, it had significant inhibitory effects on the enzymes α-amylase (72.93%) and α-glucosidase (60.48%) by ZnONP-η. The efficacy of dye degradation with synthesized nanoparticles seems to enhance with increased particle sizes and reduced specific surface areas. The antioxidant, antidiabetic, and catalytic capabilities improved with an increase in particle size. Nevertheless, it was found that an increase in particle size corresponded with a substantial reduction in antibacterial activity. The study presents an efficient approach for the eco-friendly synthesis of ZnONPs, highlighting their significant potential for many biological applications.